060 Challenging the current assessment criteria for scoring central sleep apnea at altitude. (3rd May 2021) - Bird, Jordan; Chan, Jason; Rimke, Alexander; Kalker, Anne; Chan, Garrick; Brutsaert, Tom; Sherpa, Mingma; Day, Trevor
Abstract: Introduction: Sleep disordered breathing comes in two forms: obstructive and central sleep apnea (SA). Obstructive sleep apnea (OSA) is caused by upper airway collapse during sleep, and is associated with increases in morbidity and mortality. Conversely, central sleep apnea (CSA) results from increases in respiratory chemosensitivity to blood gas challenges in the context of high-altitude ascent. CSA increases in severity and apneas shorten in duration with higher ascent and/or time spent at altitude. Although both types of SA are characterized by intermittent periods of apnea and hyperventilation, the underlying mechanisms and phenotypes between OSA and CSA are different. A universal scoring system for the two types of context-dependent SA may lead to errors in quantification. The American Association of Sleep Medicine (AASM) developed assessment criteria for SA, which are universally-utilized for all types of SA to quantify an apnea-hypopnea index (AHI; events/hour), where apneas are scored as cessation of breathing ≥10-sec. We aimed to assess the effect of reducing the apnea-detection threshold (ADT) to <10-sec to quantitatively assess the extent that a shorter ADT affects the scoring of AHI in the context of high-altitude ascent, where CSA is universal. Methods: We assessed CSA using portable polysomnography (ApneaLink, ResMed) during ascent to 5160m in the Nepal Himalaya over 10 days in 15 healthy participants. Files were archived digitally for later analysis using automated scoring software (ApneaLink Reporting Software, ResMed). We quantified and compared AHI using AASM criteria (i.e., 10-sec ADT) and a shorter 5-sec ADT. Results: AHI was 3.9±4.1 events/hour at 1045m prior to ascent, with AHI increasing to 37.5±32.8 events/hour (P<0.0001) at 5160m after 10 days of incremental ascent using AASM criteria (i.e., 10-sec ADT). When the ADT was reduced to 5-sec at 5160m, AHI was increased to 61.6±38.1 (+61%; P=0.0002). Conclusion: This preliminary report suggests that the AASM criterion for scoring apneas, which is broadly applied to OSA at low altitude, may underestimate the assessment and quantification of CSA with ascent to and prolonged stays at high altitude. Development of distinct assessment criteria for OSA and CSA may be warranted. Support (if any): Natural Science sand Engineering Research Council of Canada